Food Exposures to Lead - Kolbye, Albert C. (1974)
Exposures to lead have emanated from various sources, including food, throughout human history. Occupational and environmental exposures (especially pica) appear to account for much of the identified human disease, however, food-borne exposures deserve further investigation. Lead residues in food can result from: biological uptake from soils into plants consumed by food animals or man, usage of lead arsenate pesticides, inadvertent addition during food processing, and by leaching them improperly glazed pottery used as food storage or dining utensils. Estimates of total dietary exposure should reflect frequency distribution data on lead levels in specific food commodities in relation to the quantities actually ingested by various sample populations to distinguish degrees of risk associated with particular dietary habits. Earlier estimates of average total dietary intake of lead by adults have been reported to range from above 500 μg/day downward with more recent estimates suggesting averages of 200 μg/day or lower. The strengths and weaknesses of these data are discussed along with analytical and sampling considerations. FDA programs related to food surveillance, epidemiology, and toxicological investigation are briefly described.